Hybrid Organizations – What’s in a Name? - Hallonsten Olof; Thomasson Anna (Journal of Organizational Sociology)
Judging from the steep rise in number of publications in organizational sociology and management studies about “hybrid organizations”, it would seem as if this is either something new or something that has grown in importance in the past decades. In this article, we make a thorough attempt to provide the concept a proper anchoring in sociology and organization studies. We demonstrate that hybridity – meaning that organizations combine two or more purposes, governance forms, or logics – is both a well-known and a natural feature of organizations. But we also demonstrate that the sociological understanding of society as composed of differentiated spheres or subsystems, and the blurring of boundaries between these spheres in the past half a century (described as postmodernity, late modernity or indeed “liquid modernity”) raises the relevance of the concept “hybrid organizations”. We therefore argue that “hybrid organizations” is neither a tautological nor redundant concept but is highly relevant to a range of studies of how organizations handle multiple goals, interests, and governance modes by interpreting and respecifying logics on the overall societal level. Thus, organizations can both suffer from hybridity and make it an asset in renewal and adaptation.